PENGAPLIKASIAN YUKOM VMA SEBAGAI BANTUAN PENANGKAPAN KAPAL GILLNET DI MADASARI, KABUPATEN PANGANDARAN - Ganda Dodi Edward; Junianto Junianto (Universitas Pattimura, 2024)
One of the fishing gears operated in Pangandaran waters is Gillnet. Traditional method to find ocean fish such as star interpretation, water ripples sound caused by fish shoals, and other indicators, is mostly applied by fishers in Pangandaran. To support their fishing operation a smart fishing tool is needed such as a vessel multi aid (VMA), Created by UCT Inc. as a specific maritime telecommunication, a brand name of Yukom VMA has been cooperated to Fishing Centre of the Indonesian Ministry of Marine Affairs and Fisheries. Yukom VMA basically is a assisting tool to find potential fishing ground. The purpose of this study is to examine the effectiveness of Yukom VMA to increase fisher’ catches and their potential utilization. This study was held on August 1, 2021 to September 1, 2021. The method used is descriptive method and direct interviews. The respondents were Gillnet fishers who drop their catch at the landing site (TPI) of Madasari. The features of Yukom VMA are consisted of e-logbook, SOS for emergency, Yukom chat, navigation supports, information of fishing ground sites and weather. This study resulted that Yukom VMA application is effective to increase fisher’s catches, helps fishers to carry out fishing operation, except for fishing ground information, the sites were too far to be reached out using small boat (2-3 GT). The average catch of Madasari fishermen is 102.6 kg with an average number of trips per month 16.7 trip and an average CPUE value of 10.3 kg/trip.